PENGEMBANGAN PEMBELAJARAN ONLINE BERBASIS MICROSOFT SWAY UNTUK MENINGKATKAN PRESTASI BELAJAR ( Studi Pengembangan Pada Mata Pelajaran Informatika Siswa Kelas X SMA Negeri 1 Pagar Alam) - Ferlin Veronika (DIADIK, 2021)
The aim of this study was describe development about microsoft sway-based media and test its effectiveness on student achievement in informatics in class X SMA Negeri 1 Pagar Alam. This study used development research, with research subjects 10 students of class X IPS 2 for a limited scale, X IPS 4 for the Experiment Class and X IPS 1 for the control class. Data collection techniques using questionnaires, interviews, validation sheets and test questions. Data analysis using t-test and the average validation value of IT and media experts. After carrying out the development process, the product is validated with the results of material validation 3.46 and 3.81 categories of IT experts are very feasible to be tested and make revisions based on suggestions. After conducting a limited trial in class X IPS 2 with the results of t-count analysis 12.829 and t-table 1.734, there was a significant influence in the use of sway-based media and made revisions based on input from students. The results of the broad-scale Ciba test in the experimental and control class t-count 20.600 while the t-table is 1.669. This means that if the t-count is greater than the t-table, it means that the use of sway-based media in the experimental class has a significant effect on student achievement